2023
DOI: 10.21203/rs.3.rs-2607212/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial cellulose produced by Medusomyces gisevii on glucose and sucrose: biosynthesis and structural properties

Abstract: In this work, the effects of carbon sources and culture media on the production and structural properties of bacterial cellulose (BC) synthesized by Medusomyces gisevii have been studied. The culture medium was composed of different initial concentrations of glucose or sucrose dissolved in 0.4% extract of plain green tea. Parameters of the culture media (titratable acidity, substrate conversion degree etc.) were monitored daily for 20 days of cultivation. The BC pellicles produced on different carbon sources w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In contrast, the images taken at the highest magnification (160 KX) (Figure 8E,F) reveal that the fibers have an approximate diameter of 84 nm and do not follow a pattern of organization but are interlaced [64], which enables greater molecule retention capacity [63], especially for large carbon chains, as is the case of oil, whether in free form, dispersed or in an emulsion [5]. The SEM analysis demonstrated that the purification process and rinsing after the removal of the membranes from the metabolic broth were effective at removing any microorganisms that may be retained among the fibrils of the membrane, as no bacteria were seen in any of the images.…”
Section: Scanning Electron Microscopy (Sem) and Edsmentioning
confidence: 87%
See 1 more Smart Citation
“…In contrast, the images taken at the highest magnification (160 KX) (Figure 8E,F) reveal that the fibers have an approximate diameter of 84 nm and do not follow a pattern of organization but are interlaced [64], which enables greater molecule retention capacity [63], especially for large carbon chains, as is the case of oil, whether in free form, dispersed or in an emulsion [5]. The SEM analysis demonstrated that the purification process and rinsing after the removal of the membranes from the metabolic broth were effective at removing any microorganisms that may be retained among the fibrils of the membrane, as no bacteria were seen in any of the images.…”
Section: Scanning Electron Microscopy (Sem) and Edsmentioning
confidence: 87%
“…In contrast, the images taken at the highest magnification (160 KX) (Figure 8E,F) reveal that the fibers have an approximate diameter of 84 nm and do not follow a pattern of organization but are interlaced [64], which enables greater molecule retention capacity [63], especially for large carbon chains, as is the case of oil, whether in free form, dispersed or in an emulsion [5].…”
Section: Scanning Electron Microscopy (Sem) and Edsmentioning
confidence: 94%